Effect of the utilization of aromatic plants on diet utilization, milk production, parasitic load,and health status of dairy ewes - Boaventura Neto, Oscar (2014)
This dissertation studied the effects of aromatic plants on diet utilization, milk production, parasitic load, and health of Sarda dairy ewes. The first chapter reviewed the effects of aromatic plants and their extracts on ruminants in in vivo studies. The second chapter reported a long-term feeding trial on the effects of Carum sp., Coriandrum sp. and Satureja sp. at three doses on milk production, feed intake, blood and ruminal parameters and digestibility of lactating Sarda dairy ewes. All mixtures were eaten by the ewes without harming animal health; most milk parameters did not change; milk fatty acids were modified by the plants, especially at the highest dose; rumen pH was affected by plant and dose; NDF digestibility increased with the plants and in vivo digestibility of most nutrients increased with Satureja. The third chapter demonstrated anthelmintic effects (reduction of fecal egge count) of Satureja sp. alone or blended with Carum sp., and Coriandrum sp. in non-lactating pregnant Sarda ewes naturally infested by gastro-intestinal parasites. The fourth chapter tested effects of blends of the same plants on milk production, rumen function and health of lactating Sarda ewes. Milk production was not affected by plants; rumen pH tended to be positively affected, but rumen volatile fatty acids were not affected by the plants; bacteria communities in the ruminal liquid were affected by the plants, and archaea rumen population were not clearly affected.